Supporting workplace learning towards evidence-based practice - Poell, Rob F.; Woerkom, Marianne (Springer Netherlands, 2011)
This book brings together a range of state-of-the-art research papers addressing interventions to support learning in the workplace. The authors are experienced international scholars who have an interest in making HRD and workplace learning practices more evidence-based through practical relevant research. Although workplace learning is largely an autonomous process, many organizations want to manage it as part of their broader HRD strategy. There are limits, however, to the extent to which the complex dynamics of learning in the workplace can be guided in pre-determined desirable directions. This tension between the possible strengths of workplace learning and the limits of managing it is at the heart of this volume. The book is broken into three sections. The first section deals with workplace learning interventions, including HRD practitioners? strategies, training and development activities, and e-learning programs. The second section investigates the impact of social support, or lack thereof, in workplace learning, such as mentoring, coaching, and socialization practices. The third section addresses collective learning in the workplace, looking at teams, knowledge productivity, and collaborative capability building.